2009
DOI: 10.1016/j.jml.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Simulating language-specific and language-general effects in a statistical learning model of Chinese reading

Abstract: Many theoretical models of reading assume that different writing systems require different processing assumptions. For example, it is often claimed that print-to-sound mappings in Chinese are not represented or processed sub-lexically. We present a connectionist model that learns the print to sound mappings of Chinese characters using the same functional architecture and learning rules that have been applied to English. The model predicts an interaction between item frequency and printto-sound consistency anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
138
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(151 citation statements)
references
References 73 publications
(136 reference statements)
11
138
2
Order By: Relevance
“…The consistency score, defined by type, is a measure of the total number of friends to the total number of neighbors. Similar to the findings in English, several studies have shown consistency effects in naming Chinese characters (Fang et al, 1986;Hue, 1992;Yang, McCandliss, Shu, & Zevin, 2009). However, these studies have been inconsistent as to whether the consistency effect emerged in naming high-frequency characters.…”
supporting
confidence: 62%
See 3 more Smart Citations
“…The consistency score, defined by type, is a measure of the total number of friends to the total number of neighbors. Similar to the findings in English, several studies have shown consistency effects in naming Chinese characters (Fang et al, 1986;Hue, 1992;Yang, McCandliss, Shu, & Zevin, 2009). However, these studies have been inconsistent as to whether the consistency effect emerged in naming high-frequency characters.…”
supporting
confidence: 62%
“…Character frequency A considerable amount of evidence has indicated that character frequency is a powerful predictor of RTs in Chinese character recognition; frequency effects have been observed consistently in a wide range of tasks (Hue, 1992;Lee et al, 2005;Liu et al, 2007;Yang et al, 2009). Higher frequency characters tend to be processed more quickly than lower frequency characters during naming (Lee et al, 2005;Yang et al, 2009).…”
Section: Lexical Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, previous models of reading acquisition have made important contributions demonstrating an influence of orthographic transparency on phonological processing (Harm & Seidenberg, 1999;Yang, McCandliss, Shu, & Zevin, 2009) and semantic processing (Harm & Seidenberg, 2004;Yang, Shu, McCandliss, & Zevin, 2013). However, such models have tended to be trained on prototypical phonological representations in which substantial phonological structure is embedded, and then the processing of the phonological structure itself is investigated as both the input and output system.…”
Section: Discussionmentioning
confidence: 99%